Completing the First Year of Independence : British Official Reports from South Asia, 1 May - 17 September 1948 (Part 1 & Part 2) - Carter, Lionel, (Brill | Manohar Publishers & Distributors, 2016)
The present volume, in two parts, completes the documentation of the first year of South Asian independence as seen from British official records. This traumatic year had been marked by horrendous communal violence; mass movement of refugees; war in Kashmir; the assassination of Mahatma Gandhi (and death of Mohammed Ali Jinnah a little after its end); as well as huge economic and political problems in both India and Pakistan. The Acting British High Commissioner in India summed up the first year of India's independence graphically in September 1948 when he wrote: 'The most remarkable perhaps of the achievements of Pandit Nehru's Government is that they survived at all in face of the quite overwhelming difficulties.' The work covers a wide range of developments but two issues are at its centre - Kashmir and Hyderabad. As regards Kashmir, hopes of a settlement were raised by the arrival of the U.N. Kashmir Commission in South Asia in July 1948. However, by September it was clear that the Commission had not been immediately successful in its endeavours. Information received from Richard Symonds, an official on the Commission's staff, is included. On Hyderabad the record is one of economic warfare, frequent rumours of an Indian invasion to unite the State with India and attempts by Mountbatten, Mirza Ismail and Roy Bucher (the Commander-in-Chief of the Indian Army) to bring about a peaceful settlement. Eventually Indian forces entered the State on 13 September and the volume ends with the Nizam's capitulation on 17 September. Included as appendices are important surveys of the Hyderabad situation.